Increased Incidence of Perforated Appendicitis in Children During COVID-19 Pandemic in a Bavarian Multi-Center Study - Schäfer, Frank-Mattias; Meyer, Johannes; Kellnar, Stephan; Warmbrunn, Jakob; Schuster, Tobias; Simon, Stefanie; Meyer, Thomas; Platzer, Julia; Hubertus, Jochen; Seitz, Sigurd T.; Knorr, Christian; Stehr, Maximilian (Frontiers in Pediatrics, 2021)
Introduction: Since early 2020 the COVID-19 pandemic and statutory preventive reorganization of treatment capacities with cancellation of elective surgery as well as curfew regulations led to vastly decreased utilization of primary health care. Material and methods: To assess whether there are negative effects on pediatric acute care in Bavaria during the spring 2020 lockdown a state-wide retrospective multi-center study was performed to analyze the rate of perforated appendicitis during lockdown. Children who have been operated on during the corresponding period in 2018/19 served as control group. Results: Overall, 514 patients (292 boys, 222 girls) were included (2020: 176 patients; 2019: 181 patients; 2018: 157 patients). Median age was 11.2 yrs. 439 patients (85,4 %) underwent laparoscopic surgery, 69 (13.4 %) open surgery and 1.2 % underwent conversion from laparoscopic to open surgery. In 2020 a perforation rate of 27.8 % (49/176 patients) was found, in 2018-2019 perforation rate was 20.7 % (70/338 patients, p = 0.0359, Cochran-Mantel-Haenszel-Test). Subgroup analysis showed that in younger patients (<=11.2 years), in 2020 perforation rate was significantly higher with 37.6% (32/85 patients), while 22.2 % (39/176) in 2018/2019 (p=0.014, Fisher’s exact test).In boys perforation rate was significantly higher in 2020 with 35.0 % (35 / 100 patients) compared to 21.4 % in 2018-2019 (p=0.0165, Fisher’s exact test). Conclusion: During the period of curfew regulations in Bavaria the rate of perforated appendicitis in childhood increased significantly, especially in younger children and boys. Potentially this has to be attributed to delayed presentation to pediatric surgery care. Because of potential long-term sequelae of perforated appendicitis these adverse effects during curfew have to be taken into account for future political decision making to ensure reasonable patient care and avoid collateral damage in near-future or on-going pandemic situations.